An aggregation-prone mutant of eIF3a forms reversible assemblies escaping spatial control in exponentially growing yeast cells - Senohrabkova, Lenka; Malcova, Ivana; Hasek, Jiri (Current genetics, 2019)
Cells have elaborated a complex strategy to maintain protein homeostasis under physiological as well as stress conditions with the aim to ensure the smooth functioning of vital processes and producing healthy offspring. Impairment of one of the most important processes in living cells, translation, might have serious consequences including various brain disorders in humans. Here, we describe a variant of the translation initiation factor eIF3a, Rpg1-3, mutated in its PCI domain that displays an attenuated translation efficiency and formation of reversible assemblies at physiological growth conditions. Rpg1-3-GFP assemblies are not sequestered within mother cells only as usual for misfolded-protein aggregates and are freely transmitted from the mother cell into the bud although they are of non-amyloid nature. Their bud-directed transmission and the active movement within the cell area depend on the intact actin cytoskeleton and the related molecular motor Myo2. Mutations in the Rpg1-3 protein render not only eIF3a but, more importantly, also the eIF3 core complex prone to aggregation that is potentiated by the limited availability of Hsp70 and Hsp40 chaperones. Our results open the way to understand mechanisms yeast cells employ to cope with malfunction and aggregation of essential proteins and their complexes.
Keywords: mutace; proteiny tepelného šoku HSP70; mikrofilamenta; Saccharomyces cerevisiae Proteins; těžké řetězce myosinu; Mitochondria; myosin typu V; Myosin Heavy Chains; Protein Aggregates; eukaryotický iniciační faktor 3; Saccharomyces cerevisiae; lidé; Mutation; proteiny tepelného šoku HSP40; Myosin Type V; mitochondrie; HSP70 Heat-Shock Proteins; proteinové agregáty; Eukaryotic Initiation Factor-3; HSP40 Heat-Shock Proteins; Saccharomyces cerevisiae - proteiny; Actin Cytoskeleton; Humans